Knowledge of acute kidney injury among nurses in two government hospitals in Ondo City, Southwest Nigeria - Oluseyi A Adejumo; Ayodeji A Akinbodewa; Oladimeji E Alli; Olufemi B Pirisola; Olatunji S Abolarin (Saudi Journal of Kidney Diseases and Transplantation, 2017)
Adequate knowledge of acute kidney injury (AKI) among all health-care providers is essential for early diagnosis and management to reduce the associated burden. This study determined the knowledge of AKI among nurses in two government hospitals in Ondo City, Southwest Nigeria. This cross-sectional descriptive study was carried out in two government hospitals in Ondo City using a self-administered pretested questionnaire that assessed knowledge of AKI and associated factors. A total of 156 respondents participated in the study. Majority were between 20 and 40 years of age and were females. Ninety-nine (63.5%) had ≤10 years of nursing experience. A total of 106 (67.5%) respondents had received formal lectures on AKI in the past. Only 12 (7.7%) respondents had good knowledge of AKI, 98 (62.8%) had fair knowledge, and the remaining 46 (29.5%) had poor knowledge of AKI. There was a significant association between the knowledge of AKI and having received previous AKI lectures (P = 0.03), but knowledge was not associated with the years of nursing experience (P = 0.37). There was a significant association between having received previous AKI lecture and knowledge of AKI. We, therefore, recommend regular in-service training on AKI for practicing nurses.